2021
DOI: 10.1002/smtd.202101158
|View full text |Cite
|
Sign up to set email alerts
|

Engineering CXCL12 Biomimetic Decoy‐Integrated Versatile Immunosuppressive Nanoparticle for Ischemic Stroke Therapy with Management of Overactivated Brain Immune Microenvironment

Abstract: Following ischemic stroke, brain‐resident activated microglia and peripherally infiltrated inflammatory cells create a complicated and overactivated brain immune microenvironment, which causes neuron death and dramatically hinders neurological functional recovery. Herein, an engineering CXCL12 biomimetic decoy‐integrated versatile immunosuppressive nanoparticle (VIN) for management of the overactivated brain immune microenvironment is reported. The shell of VIN (membrane of CXCR4 overexpressed mesenchymal stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 55 publications
0
54
0
Order By: Relevance
“…Recent studies reported that macrophage repolarization from M1 to M2 relieved the inflammation and promoted neuro‐protection. [ 11,40 ] Although natural melanin nanoparticles were reported to polarize tumor‐associated macrophages from M2 to M1 in tumors, [ 41 ] emerging evidence showed that melanin nanoparticles could repolarize M1 to M2 macrophages in acute liver injury, [ 33 ] myocardial infarction, [ 42 ] and acute kidney injury, [ 43 ] which may be attributed to the different microenvironments. We investigated the anti‐inflammatory effects of AMEC using macrophages which were double labeled with F4/80 and CD11b in the injury site.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that macrophage repolarization from M1 to M2 relieved the inflammation and promoted neuro‐protection. [ 11,40 ] Although natural melanin nanoparticles were reported to polarize tumor‐associated macrophages from M2 to M1 in tumors, [ 41 ] emerging evidence showed that melanin nanoparticles could repolarize M1 to M2 macrophages in acute liver injury, [ 33 ] myocardial infarction, [ 42 ] and acute kidney injury, [ 43 ] which may be attributed to the different microenvironments. We investigated the anti‐inflammatory effects of AMEC using macrophages which were double labeled with F4/80 and CD11b in the injury site.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Jiang et al ( 2021 ) have elucidated that cGAS knockdown improved M2 phenotype polarization of microglia to attenuate microglial inflammatory response by hindering the cGAS-STING signal axis in mice with stroke, highlighting that such signal axis can be used as a potential therapeutic target. Subsequently, the experiment performed by Shi et al ( 2022 ) also demonstrated that inhibiting the cGAS-STING pathway through a cGAS inhibitor integrated versatile immunosuppressive nanoparticle in microglia contributed to improving an anti-inflammatory phenotype polarization in rats following stroke.…”
Section: Potential Therapeutic Targets and Strategies Of Microglia-in...mentioning
confidence: 99%
“…Inflammatory cytokines are then released by activated microglia and peripheral leucocytes, which enhance the inflammatory response. Studies have reported that elevated inflammatory markers are associated with the risk of stroke recurrence and less favorable outcomes [ 39 , 40 ]. Several events such as reperfusion of tissue, oxidative stress, and microglial activity can promote cell death in the penumbra region, which can lead to secondary neuronal death and further increased damage to stroke area [ 41 ].…”
Section: Strokementioning
confidence: 99%